1979
DOI: 10.1113/jphysiol.1979.sp012891
|View full text |Cite
|
Sign up to set email alerts
|

Calcium carrying system in the giant muscle fibre of the barnacle species, Balanus nubilus

Abstract: SUMMARY1. Single barnacle muscle fibres from Balanus nubilus were internally perfused with an isotonic solution containing 180 mM-tetraethylammonium acetate and the effects of Ca concentration in the external solution on the voltage-clamp currents, especially the initial inward current, were examined.2. Muscle fibre in external solution containing no added Ca (concentration of Ca < 10-5 M) gave a current-voltage curve that showed a small inward current followed by a small outward current. An identical curve wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…They found that K'c a ranged between 25 and 40 mM. As discussed below, the dissocia tion constant is affected by the high [MgH]o and would be smaller in the absence of Mg2+ Beirao & Lakshminarayanaiah (1979). studied the same effect on barnacle muscle,but in a volta & c-clamp experiment where I Ca wa�, directly measured.…”
mentioning
confidence: 92%
“…They found that K'c a ranged between 25 and 40 mM. As discussed below, the dissocia tion constant is affected by the high [MgH]o and would be smaller in the absence of Mg2+ Beirao & Lakshminarayanaiah (1979). studied the same effect on barnacle muscle,but in a volta & c-clamp experiment where I Ca wa�, directly measured.…”
mentioning
confidence: 92%
“…Voltage-clamp studies of the barnacle muscle (Keynes et al, 1973;Hagiwara et al, 1969;Hagiwara et al, 1974;Murayama and Lakshminarayanaiah, 1977;Beirao and Lakshminarayanaiah, 1979) indicate that the fiber possesses a simple conductance system consisting of voltage dependent Ca"+ and K+ channels, neither of which inactivates appreciably. Currentclamp studies, however, show complicated oscillatory voltage behavior Murayama and Lakshminarayanaiah, 1977).…”
Section: Introductionmentioning
confidence: 99%